Image Scanning Microscopy to Investigate Polycomb Protein Colocalization onto Chromatin - Irene Nepita; Simonluca Piazza; Martina Ruglioni; Sofia Cristiani; Emanuele Bosurgi; Tiziano Salvadori; Giuseppe Vicidomini; Alberto Diaspro; Marco Castello; Paolo Bianchini; Barbara Storti; Ranieri Bizzarri (Applied Sciences, 2023)
Super-resolution microscopy has been recently applied to understand the 3D topology of chromatin at an intermediated genomic scale (kilobases to a few megabases), as this corresponds to a sub-diffraction spatial scale crucial for the regulation of gene transcription. In this context, polycomb proteins are very renowned gene repressors that organize into the multiprotein complexes Polycomb Repressor Complex 1 (PRC1) and 2 (PRC2). PRC1 and PRC2 operate onto the chromatin according to a complex mechanism, which was recently recapitulated into a working model. Here, we present a functional colocalization study at 100–140 nm spatial resolution targeting PRC1 and PRC2 as well as the histone mark H3K27me3 by Image Scanning Microscopy (ISM). ISM offers a more flexible alternative to diffraction-unlimited SRMs such as STORM and STED, and it is perfectly suited to investigate the mesoscale of PRC assembly. Our data suggest a partially simultaneous effort of PRC1 and PRC2 in locally shaping the chromatin topology.